How to govern the digital transformation of health services - Ricciardi, Walter; Pita Barros, Pedro; Bourek, Aleš; Brouwer, Werner; Kelsey, Tim; Lehtonen, Lasse; Expert Panel on Effective Ways of Investing in Health (EXPH) (European journal of public health, 2019)
The impact of digitalization of health services has been profound and is expected to be even more profound in the future. It is important to evaluate whether digital health services contribute to health system goals in an optimal way. This should be done at the level of the service, not the 'digital transformation'. Decisions to adopt new digital health services, at different levels of the health care system, are ideally based on evidence regarding their performance in light of health system goals. In order to evaluate this, a broad perspective should be taken in evaluations of digital health services. Attainment of the broad health system goals, including quality, efficiency and equity, are objectives against which to judge new digital health services. These goals in a broad sense are unaltered by the process of digitalization. Governance should be designed and tailored in such a way to capture all relevant changes in an adequate way. When evaluating digital health services many specific aspects need to be considered. Like for other innovations and (new) technologies, such promises may or may not materialize and potential benefits may also be accompanied by unintended and/or negative (side) effects in the short or long term. Hence, the introduction, implementation, use and funding of digital health technologies should be carefully evaluated and monitored. Governments should play a more active role in the further optimization both of the process of decision making (both at the central and decentral level) and the related outcomes. They need to find a balance between centralized and decentralized activity. Moreover, the broader preparation of the health care system to be able to deal with digitalization, from education, through financial and regulatory preconditions, to implementation of monitoring systems to monitor its effects on health system performance remains important.
Keywords: vláda; technologie; politika; Telemedicine; telemedicína; Politics; Health Services Administration; rozhodování; Decision Making; Health Services; Humans; informační systémy; zdravotnické služby; Information Systems; Government; řízení zdravotnictví; Delivery of Health Care; Technology; poskytování zdravotní péče; lidé